Hubungan Tingkat Hunian Pengunjung Homestay terhadap Tingkat Pendapatan Owners di Desa Bontomarannu Kecamatan Uluere Kabupaten Bantaeng Provinsi Sulawesi Selatan - Suardi Suardi; Muhammad Yusuf Yunus (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
This study aims: to determine the relationship between visitor occupancy rates and the income level of owners of tourist homestays in Bontomarannu Village, Uluere District, Bantaeng Regency. The analytical method used 1) Simple Regression Analysis which is to find out the form of relationship between visitor occupancy rates (X) and owners (Y) income. 2) Simple correlation analysis is used to determine the closeness of relationship between two variables and to find out the direction of the relationship that occurs. 3) The Determination Coefficient can be used to find out how much the percentage of homestay relationships (variable X) to owners (Y) income. The results of this study indicate: 1) The number of visitors both local and foreign tourists fluctuate every month, except for 2 consecutive months, namely in April - May 2017 experiencing a decrease due to coinciding with the holy month of Ramadan and Idhul Fitri the majority of people in the village of Bontomarannu, are Muslim. 2) Based on the results of the calculation of correlation analysis, then r = 0.99, which means that there has been a perfect and positive linear relationship between variables x and y variables. 3) Based on the calculation in table t for a 5% error at df = n-2, obtained t table 1.701. It turns out that t count is 23.30> t table 1.701 thus, then the alternative hypothesis  is accepted and null hypothesis  is rejected, the conclusion is significant relationship between occupancy rate of visitors and income level of owners.